The poor men and the amazonian land in the literary production of Euclides da Cunha - Damasceno, Bruno de Brito (Em Perspectiva, 2017)
The paper seeks to analyze the interpretations constructed by Euclides da Cunha (1867-1909) on human presence in the Amazon in the early twentieth century. The whiter analyzes that the Amazonian nature promoted a selection process, where only the most physiologically adapted were able to withstand the demands imposed by the “green hell”. And in spite of the scientific concepts that glimpsed the mestizo as a degenerate of the races and, therefore, causing the backwardness of the country, Euclides, for least with regard to the “clearing of the Amazon” inverts the order, and exalts the figure of the poor migrant, the only one capable of dominating the nature of the region and to enable your insertion into the entirety of the nation. However, Euclides also observes the perverse character of the routine of forest workers, with physical punishment and impediment of possession of worked land. For the author, the omission of the State with the structure of relations of work within the rubber plantations prevented the formation of a collective feeling of nationality, and intensified his disappointment with the destiny of the Republic.